APPLICATION OF CHICKEN MANURE AND SHADING ON CARROT (Daucus carota L.) GROWTH AND YIELD. - Try Zulchi PH; Tatik Wardiyati; Mudji Santoso (The Indonesian Green Technology Journal, 2012)
Carrot is a highland plant that is mostly grown in monoculture and intercropping systems. There are even some were grown under / between perennial trees. However, this system causes the decline of light intensity,  nutrient and water. In line with this phenomenon, a research was conducted to determine the influence of chicken manure and shading on carrot’s growth and yield.  The research was conducted in the Junggo Village, Batu city, using Split Plot Design. There were two treatments i.e: (1) as main plot, namely the percentage of shading consisting of four levels:  0 %, 20 %, 40 % and 60 %. The shading material used was black plastic net; (2) as sub plot, namely chicken manure dosage consisting of three levels: 10 tons/ha, 20 tons/ha and 30 tons/ha. The twelve treatment combinations obtained were replicated three times. The result showed that the treatment of 20 tons/ha chicken manure onto carrot grown with no shading increased the growth and yield. This treatment, however, did not show a significant difference in the growth and yield when applied to carrot grown with shading. The treatment of 20% shading, yielded a good plant growth although accompanied by the decrease in the fresh tuber weight by 14 % and the increase in beta carotene content. The application of 10 tons/ha did not show difference in the growth and yield of carrot treated with 20 tons/ha and 30 tons/ha of chicken manure. Keywords:  carrot, chicken manure, shade.